ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris pada Perusahaan Manufaktur yang Listing Di Bursa Efek Indonesia 2010-2013) - Sarah Denia Novianti (MNJ 16 UMY 230, 2016)
This study aims to determine the factors that affect audit delay in manufacturing companies listed on the Bursa Efek Indonesia 2010-2013. The factors studied were profitability (Prof), auditor's opinion (OP), the size of the company (UP), accounting public office’s size (UKAP), and the complexity of the operation (KO). Samples were selected based on purposive sampling method. Samples obtained from sixty-six companies listed in the Indonesia Stock Exchange with the observation for four years, so that the selected sample as many as 264 samples. The analytical method used is descriptive analysis, a classic assumption test and multiple regression test. Multiple regression test results indicate that the audit delay is significantly influenced by the size of the firm. And adjusted R2 value of 8.4% of these results it can be concluded that the profitability, the auditor's opinion, the size of the company, accounting public office’s size and operational complexity is only able to explain the audit delay of 8.4%. Keywords: audit delay, profitability, the auditor's opinion, company’s size, KAP size, operational complexity.